Informational campaign effects of the Nutrition Labeling and Education Act (NLEA) of 1990 on diet - Asirvatham, Jebaraj (Cogent social sciences, 2017)
This study examines consumer response to a mass-media educational campaign undertaken as part of the Nutrition Labeling and Education Act (NLEA) of 1990, employing media content analysis. Time and spatial variation in the nutrition-label information dissemination in the newspaper media were modeled in a difference-in-difference framework. The goal, however, is not to assess newspaper as a source, but to understand the impact of how nutrition information is portrayed. We find limited impact of the media informational campaign. Articles that portrayed Nutrition Facts Labels in a positive way decreased sugars intake from labeled foods. Interestingly, articles that portrayed Nutrition Facts Labels negatively had more impact on unlabeled foods. The findings give insights into communication of nutrition information to the public.